PERTANGGUNGJAWABAN PIDANA DALAM KEJAHATAN SIBER TERHADAP INFRASTRUKTUR DIGITAL NEGARA MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI KASUS PERETASAN PUSAT DATA NASIONAL SEMENTARA 2 INDONESIA) - Muhammad Faeyza Rabbani Harahap; Aan Asphianto; Reine Rofiana (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2026)
The development of information and communication technology has had a positive impact in various areas of life, including government systems. However, on the other hand, this development has also given rise to new forms of digital crime, one of which is cybercrime that targets a country's digital infrastructure. One case that emerged in Indonesia was the hacking of the Temporary National Data Center 2 (PDNS 2) in June 2024, which resulted in disruptions to 239 government agencies and large-scale data leaks. This study aims to analyze the forms of cybercrime against the country's digital infrastructure based on the theory of cybercrime in Indonesian criminal law and to examine the criminal liability of the perpetrators of the PDNS 2 hack. The research method used is normative juridical with a legislative and case study approach. The data used was sourced from primary and secondary legal materials, including official reports from BSSN and several news media publications. The results of the study show that the hacking of PDNS 2 is a form of cybercrime that falls under the category of unauthorized access to computer systems and services and cyber sabotage, which can be charged under the provisions of Articles 30, 32, 52, and 46 of the ITE Law and Article 482 of the Criminal Code. Although there has been no legal action against the perpetrators to date, normatively, the elements of criminal liability have been fulfilled, including the existence of unlawful acts, fault, the ability to be held responsible, and the absence of justifiable or exculpatory reasons.Keywords: Cyber Crime, State Digital Infrastructure, Hacking, Criminal Liability, ITE Law